2007
DOI: 10.5433/1679-0375.2007v28n2p99
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do efeito da condutividade na eletro-coagulação-flotação aplicada ao tratamento físico-químico de águas residuárias

Abstract: ResumoEste trabalho estudou o efeito da condutividade na aplicação simultânea dos princípios da eletrólise da água, da coagulação química e da flotação no tratamento de águas residuárias com elevado teor de matéria em suspensão, como forma de caracterizar a eletro-coagulação-flotação (ECF). Apresentamse resultados dos experimentos realizados na instalação piloto implantada e operada no Laboratório de Controle Ambiental, no campus da Unicamp em Limeira. A ECF se desenvolveu em um reator eletrolítico, onde a águ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the biological treatment, the organic matter (OM) removal was carried out by bacteria, producing carbon dioxide, water and organic flakethat would grow in the aeration tank and form the biomass to be sedimented in the decanter (Foco & Téran, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the biological treatment, the organic matter (OM) removal was carried out by bacteria, producing carbon dioxide, water and organic flakethat would grow in the aeration tank and form the biomass to be sedimented in the decanter (Foco & Téran, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary decanted sludge was returned by pumping ( Figure 3) to the aeration tank to increase the system efficiency (Foco & Téran, 2007). It was found that the operating cost was quite high due to energy consumption for moving the equipment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation